(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article reveals the peculiarities of using different methods of attracting students to the lesson and making them interested in the lesson using games in foreign language classes.